2021
DOI: 10.1038/s41388-021-01664-1
|View full text |Cite
|
Sign up to set email alerts
|

H2A.Z overexpression suppresses senescence and chemosensitivity in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most intractable and devastating malignant tumors. Epigenetic modifications such as DNA methylation and histone modification regulate tumor initiation and progression. However, the contribution of histone variants in PDAC is unknown. Here, we demonstrated that the histone variant H2A.Z is highly expressed in PDAC cell lines and PDAC patients and that its overexpression correlates with poor prognosis. Moreover, all three H2A.Z isoforms (H2A.Z.1, H2A.Z.2.1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Three incorrectly classified samples were from Wang et al (2019): SK-Hep1 cells treated with XL413, which were described as non-senescent due to their wild-type TP53 status but scored as senescent by the classifier (score of 0.81); and PLC and Hep3B cells treated with XL413, which were defined as senescent, but received a non-senescent score (0.10 and 0.37, respectively). The H2A.Z knockdown samples from Á vila-Ló pez et al (2021) were also not classified as senescent, but it should be noted that although these samples were described as senescent, they contained fewer than 50% of senescent cells (Á vila-Ló pez et al, 2021). This indicates that the classifier may only classify a sample as senescent if the majority of cells are senescent.…”
Section: Sencan Classifier For Cancer Cell Senescencementioning
confidence: 96%
“…Three incorrectly classified samples were from Wang et al (2019): SK-Hep1 cells treated with XL413, which were described as non-senescent due to their wild-type TP53 status but scored as senescent by the classifier (score of 0.81); and PLC and Hep3B cells treated with XL413, which were defined as senescent, but received a non-senescent score (0.10 and 0.37, respectively). The H2A.Z knockdown samples from Á vila-Ló pez et al (2021) were also not classified as senescent, but it should be noted that although these samples were described as senescent, they contained fewer than 50% of senescent cells (Á vila-Ló pez et al, 2021). This indicates that the classifier may only classify a sample as senescent if the majority of cells are senescent.…”
Section: Sencan Classifier For Cancer Cell Senescencementioning
confidence: 96%
“…Notably, two distinct isoforms of H2AZ variant histone, namely H2AZ1 and H2AZ2 that are encoded by two non-allelic genes and differ only by three amino acids, are overexpressed in multiple cancers [ 12 15 ]. Like their canonical counterparts, the main function of variant histone proteins is to generate nucleosomes for genome organization within the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…For these proteins, there are already multiple studies in connection with PDAC to be found in the literature. H2A.Z isoforms were reported to be overexpressed in PDAC cell lines and PDAC tissues, resulting in tumor growth and resistance to chemotherapy [ 23 ]. In this study, Avila-Lopez et al demonstrated that the depletion of H2A.Z isoforms promotes tumor senescence, increases sensitivity to the chemotherapeutic drug gemcitabine, and decreases tumor growth in a mouse xenograft model in vivo.…”
Section: Discussionmentioning
confidence: 99%